PENGARUH KOMPENSASI TERHADAP RETENSI KARYAWAN MELALUI KEPUASAAN KERJA DAN KOMITMEN AFEKTIF PADA BEBERAPA RUMAH SAKIT DI DKI JAKARTA - Diah Puji Astuti; Mutiara Sibarani Panggabean (Jurnal Manajemen dan Pemasaran Jasa, 2014)
This research refers to a previous study conducted by Anis et al., (2011); Chee Hong et al., (2012) and completed by Lamba & Choudhary (2013). This research is about “Compensation effect on the retention of employees through job satisfaction and affective commitment in several hospitals in Jakarta”. The background of this research is to analyze the Employee Retention refers to the policy of the hospital to prevent the employee out of the hospital. The purpose of this research was to examine the effect of Compensation for Employee Retention Through Work Attitude. The design of this research using primary data obtained by distributing questionnaires to 105 Hospital of type C in Jakarta. Data analysis method used is Structural Equation Model (SEM). The results of this research concluded that there is a positive influence through the Employee Retention Compensation for Work Attitude.Keywords: Compensation, Employee Retention, Job Satisfaction, Affective commitment, Hospital